Lobster Clear Seeds Smuggling’s Threats and Modes Through the Customs Side in Indonesia - Indradinata, Bayu; Samputra, Palupi Lindiasari (International Journal Labs, 2023)
Background: Indonesia is one of the countries that has a very diverse biodiversity in the world and is one of the strengths of Indonesia's natural resources. One of Indonesia's leading natural resources is lobster. Lobster commodities have a very high export value and have a wide market share in the world. However, the existence of lobsters is currently under threat considering the massive smuggling of lobster clear seeds which are lobster seeds for cultivation. The threat of smuggling and uncontrolled fishing of lobster clear fry threatens the resilience of lobster clear seeds in the wild. Aim: The purpose of the research was to determine the threat of smuggling lobster clear seeds and the mode of smuggling carried out by smugglers. Method: This research is a quantitative research with a statistical descriptive analysis method using secondary time series data with a case study approach to smuggling enforcement carried out by the Directorate General of Customs and Excise for the period 2018 – 2022. Findings: Benur smuggling still often occurs in Indonesia by utilizing illegal entrances through sea routes and international airports, supported by indications of the involvement of unscrupulous officials and organized international crime networks.